2021
DOI: 10.32800/abc.2021.44.0213
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the nocturnal activity of birds during the COVID–19 pandemic lockdown in a neotropical city

Abstract: The COVID–19 lockdown provided the opportunity to measure species biodiversity in urban environments under conditions divergent from regular urban rhythms. For 90 days, including weeks of strict lockdown and the subsequent relaxation of restrictions, we measured the presence and abundance of birds that were active at night at two sites in the city of Cali, Colombia. Our results show that species richness of nocturnal birds decreased 40 % to 58 % during the weeks with more human activity, adding further evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…This indicates that the severe reduction in human activity during the COVID-19 lockdown in almost half of our survey sites was drastic, showing an increase of at least one-fourth in species richness during the strict lockdown period. It is noteworthy that the strict lockdown lasted only six weeks, and in this short window of time many bird species responded swiftly -as seen in other studies (Gordo et al, 2021, Sanderfoot et al, 2022-and with a similar pattern for nocturnal species (Estela et al, 2021), making local assemblages more diverse, particularly those from low-intensity urbanization sites.…”
Section: Variablessupporting
confidence: 67%
“…This indicates that the severe reduction in human activity during the COVID-19 lockdown in almost half of our survey sites was drastic, showing an increase of at least one-fourth in species richness during the strict lockdown period. It is noteworthy that the strict lockdown lasted only six weeks, and in this short window of time many bird species responded swiftly -as seen in other studies (Gordo et al, 2021, Sanderfoot et al, 2022-and with a similar pattern for nocturnal species (Estela et al, 2021), making local assemblages more diverse, particularly those from low-intensity urbanization sites.…”
Section: Variablessupporting
confidence: 67%
“…We moreover demonstrate that bird activity patterns can differ on a local scale only hundreds of meters apart. This complexity might explain the contradicting effects of lockdown reported by others (Gordo et al, 2021;Estela et al, 2021;Schrimpf et al, 2021;Manenti et al, 2020). It points towards the importance of monitoring activity in fine-scale across geographical and environmental landscapes and of including environmental parameters in statistical models.…”
Section: Discussionmentioning
confidence: 94%
“…Our results picture a complex and dynamic urban ecological system where animal activity depends on species and site, as well as on environmental parameters and heterospecific (e.g., human) activity. This complexity might explain the contradicting effects of lockdown reported by others (Gordo et al, 2021;Estela et al, 2021;Schrimpf et al, 2021;Manenti et al, 2020). It points towards the importance of monitoring activity across geographical and environmental landscapes and of including representative parameters in statistical models.…”
Section: Discussionmentioning
confidence: 94%
“…They found that noise, population density, building height and proportion of commercial buildings have negative impacts on bird presence. Additionally, Estela et al (2021) examined how the nocturnal activity of birds in the tropical city of Cali, Colombia changed during the COVID-19 pandemic lockdown and found that there was an increase in bird activity during the strict circulation period, highlighting the impacts of changes in human activity on urban biodiversity.…”
Section: Protecting Biodiversitymentioning
confidence: 99%